A geospatial assessment of bio-thermal influence around Çatalagzı power plant region. Issue 26 (13th December 2022) - Faizi, Fiza; Basit, Iqra; Mahmood, Khalid; Yildrim, Yilmaz; Bilgili, Mehmat Sinan; Mushtaq, Fatima
Abstract: Combustion of coal in thermal power plants poses significant threat to surrounding ecology, by the release of harmful effluents. This study assesses the bio-thermal impact of emissions from Catalagzı Thermal Power Plant Region (CTPPR). A geospatial analytical framework has been modeled, utilizing satellite-based bio and thermal indicators. Average hazardous bio and thermal influence zones around CTPPR have been found to be 1465 m and 1380 m, respectively. Bio-influence zone extent depends upon a combination of meteorological factors, whereas, the bio-hazard severity depends mainly on atmospheric temperature. Thermal influence extent is inversely related to seasonal temperature, whereas corresponding severity depends upon local heat sinks as well. Collectively, hazardous bio-thermal influence in the surroundings of CTPPR shows spatial constancy over long term. The study concludes usefulness of satellite-based economical alternatives for monitoring area under stress around CTPPR for sustainable environmental management of ecological landscapes, needed to improve the human-environment nexus. Highlights: Investigation of Thermal Power Plant (T P P) as source of environmental pollution Dynamic geospatial bio-monitoring of vegetation using satellite-based VIs is done Geospatial analysis reveals details of zones of hazardous bio-influence around T P Ps. Identified factors determining extent and severity of hazard by T P P emissions. Effectiveness of geospatial technology for ecological assessment is demonstrated